Photocatalytic Dehydrogenation of Formic Acid on CdS Nanorods through Ni and Co Redox Mediation under Mild Conditions. Issue 15 (15th July 2018) - Nasir, Jamal Abdul; Hafeez, Muhammad; Arshad, Muhammad; Ali, Naveed Zafar; Teixeira, Ivo F.; McPherson, Ian; Zia‐ur‐Rehman,; Khan, M. Abdullah
Abstract: Selective release of hydrogen from formic acid (FA) is deemed feasible to solve issues associated with the production and storage of hydrogen. Here, we present a new efficient photocatalytic system consisting of CdS nanorods (NRs), Ni, and Co to liberate hydrogen from FA. The optimized noble‐metal‐free catalytic system employs Ni/Co as a redox mediator to relay electrons and holes from CdS NRs to the Ni and Co, respectively, which also deters the oxidation of CdS NRs. As a result, a high hydrogen production activity of 32.6 mmol h −1 g −1 from the decomposition of FA was noted. Furthermore, the photocatalytic system exhibits sustained H2 production rate for 12 h with sequential turnover numbers surpassing 4×10 3, 3×10 3, and 2×10 3 for Co–Ni/CdS NRs, Ni/CdS NRs, and CoCl2 /CdS NRs, respectively. Abstract : Ni/Co Co‐op : Efficient visible light diversion dehydrogenation of formic acid over CdS nanorods through cooperative redox mediation of Ni and Co is achieved at room temperature.